Pengaruh Jenis Anoda Microbial Fuel Cells Terhadap Power Density dan Penyisihan Kandungan Organik Limbah Cair Industri Tahu - M. Ardiansyah Dwi Tama M. Ardiansyah Dwi Tama; Yayok Suryo Purnomo Yayok Suryo Purnomo; Syadzadhiya Qothrunada Zakiyayasin Nisa' Syadzadhiya Qothrunada Zakiyayasin Nisa' (Jurnal Serambi Engineering, 2024)
Tofu industry production activities generate wastewater from soy milk coagulation and moulding processes. The high content of organic compounds in tofu industry wastewater, including COD, requires treatment before discharge into water bodies. The high organic content in this wastewater can be used as a substrate in MFC systems. This research aims to analyse the effect of different anode types in the combination of MFCs-ABR reactors on the power density (mW/m²) and COD removal efficiency of tofu industry wastewater. The research method is quantitative, starting with seeding and acclimatization for 21 days, and then analysing the effect of graphite carbon and stainless steel anodes on the performance of MFCs-ABR reactors with different retention times of 24, 48, 72, 96 hours. The results showed that the graphite carbon anode produced the highest power density of 204.13 mW/m² and COD removal efficiency of 60.42% at a retention time of 96 hours.